Pengaruh Price Discount, Free Shipping Dan Online Store Atmosphere Terhadap Minat Beli Konsumen Pada Live Streaming Tiktok Shop - Kartika, Asnita; Jaya, Rama Chandra (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study analyzes the effect of price discounts, free shipping, and online store atmosphere on purchase intention in TikTok Shop's live streaming. The research method used is quantitative, with a sample of 100 respondents collected through Google Forms distributed on social media platforms. Using three independent variables (Price Discount, Free Shipping, and Online Store Atmosphere) and one dependent variable (Purchase Intention), the results showed that Price Discount (sig. 0.000), Free Shipping (sig. 0.034), and Online Store Atmosphere (sig. 0.000) each have a positive and significant effect on Purchase Intention. Simultaneously, the three independent variables have also been proven to significantly affect purchase intention. The coefficient of determination test results show that price discounts, free shipping, and online store atmosphere can explain 76.1% of the variation in purchase intention, while other factors outside the research model explain the remaining 23.9%. These findings provide practical implications for online stores to pay attention to discount pricing strategies, provide free shipping services, and create an attractive online store atmosphere in order to increase consumer buying interest effectively.